Proceedings of the 8th ACM Conference on Electronic Commerce 2007
DOI: 10.1145/1250910.1250939
|View full text |Cite
|
Sign up to set email alerts
|

Recommender systems and their impact on sales diversity

Abstract: This paper examines the effect of recommender systems on the diversity of sales. Two anecdotal views exist about such effects. Some believe recommenders help consumers discover new products and thus increase sales diversity. Others believe recommenders only reinforce the popularity of already popular products. This paper is a first attempt to reconcile these seemingly incompatible views. We explore the question in two ways. First, modeling recommender systems analytically allows us to explore their path depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 20 publications
2
67
0
Order By: Relevance
“…Indeed, Bodapati (2008) showed that product awareness is a necessary condition for actual purchase. Further, according to Fleder and Hosanger (2007), recommendation agents impact sales diversity. Intuitively, preference relaxation allows for the consideration of products that are filtered out when using logical filtering approaches.…”
Section: Hypothesesmentioning
confidence: 99%
“…Indeed, Bodapati (2008) showed that product awareness is a necessary condition for actual purchase. Further, according to Fleder and Hosanger (2007), recommendation agents impact sales diversity. Intuitively, preference relaxation allows for the consideration of products that are filtered out when using logical filtering approaches.…”
Section: Hypothesesmentioning
confidence: 99%
“…If a paper only describes the authors' previous work, then we replaced it with the previous papers of the same authors. We also excluded problem-raising papers that accentuated the im-portance of beyond-accuracy aspects based on real-world data [5] or simulation [22]. Ultimately, we selected 72 papers for review.…”
Section: Selection Of Surveyed Papersmentioning
confidence: 99%
“…It is well known that collaborative filtering (CF), one of the popular algorithms in the literature of recommendation systems, is accurate, but it recommends users the items similar to each other. Relatively recently, studies have repeatedly pointed out that beyond-accuracy aspects-such as the diversity and novelty of the recommended items-should be considered alongside accuracy [22], [45].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is difficult to apply in "user-to-user" recommendation systems due to the lack of user information and explicit user interests. Collaborative filtering is a popular recommendation whose idea is to discover similar users and recommend their commonly interested items by generating a comparable weighted recommendation value [7]. D. Agarose et al and Y. Koren adopted latent factor matrix decomposition to collaborative filtering [1,2,10].…”
Section: Related Workmentioning
confidence: 99%